(untitled) (London Journal of Research In Computer Science and Technology, 2025)
The dataset of competitors performance in some recent years is the input of winner-domain algorithm selecting good student as member of a subject team participating in Vietnam national prize. The data of learning performance features may be retrieved from the competitors learning outcomes. Meanwhile, the collection of non-learning performance feature data of competitors meets challenges relating to the individual right and interviewees cooperation for answering questionnaire. This research analyzed competitors skills and lifestyle into very simple questions with very easy answer mode, without the deep relation to their individual lifestyle. The reply-matrix and reply-cube are formed to map simple answers of questionnaire reply into quantitative values. This approach may be flexibly applied to easily form the datasets of competitors performance for various subjects in different years and at different levels of competitions.